Acceptability of a home-based visual field test (Eyecatcher) for glaucoma home monitoring: a qualitative study of patients' views and experiences. Issue 4 (5th April 2021) - Jones, Lee; Callaghan, Tamsin; Campbell, Peter; Jones, Pete R; Taylor, Deanna J; Asfaw, Daniel S; Edgar, David F; Crabb, David P
Abstract : Objectives: To explore the acceptability of home visual field (VF) testing using Eyecatcher among people with glaucoma participating in a 6-month home monitoring pilot study. Design: Qualitative study using face-to-face semistructured interviews. Transcripts were analysed using thematic analysis. Setting: Participants were recruited in the UK through an advertisement in the International Glaucoma Association (now Glaucoma UK) newsletter. Participants: Twenty adults (10 women; median age: 71 years) with a diagnosis of glaucoma were recruited (including open angle and normal tension glaucoma; mean deviation=2.5 to −29.9 dB). Results: All participants could successfully perform VF testing at home. Interview data were coded into four overarching themes regarding experiences of undertaking VF home monitoring and attitudes towards its wider implementation in healthcare: (1) comparisons between Eyecatcher and Humphrey Field Analyser (HFA); (2) capability using Eyecatcher; (3) practicalities for effective wider scale implementation; (4) motivations for home monitoring. Conclusions: Participants identified a broad range of benefits to VF home monitoring and discussed areas for service improvement. Eyecatcher was compared positively with conventional VF testing using HFA. Home monitoring may be acceptable to at least a subset of people with glaucoma.